การประเมินเงินกองทุนทางเศรษฐศาสตร์ด้วยวิธีตัวแบบคณิตศาสตร์ประกันภัย สำหรับความเสี่ยงด้านการปฏิบัติการในธุรกิจประกันภัย - นรีรัตน์ รัตนพรชัยกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
To assess economic capital for operational risk in insurance business using internal operational loss data according to Advanced Measurement Approaches (AMA). Recently, a trend in management and measurement of the operational risk for insurance industry is based on a Basel-based framework. The assumption of this research is solely based on Poisson distribution for loss frequency data. The result has indicated that the economic capital measured by value-at-risk (VaR) at 99% confidence level is not much different from the amount calculated by Basic Indicator Approach (BIA). An adjustment of parameter (lambda) upward and downward has highlighted that an increase in the parameter have a significant impact on the capital much more than a decrease in the parameter from the same adjusted levels. A commonly used method of summation of VaR measures with full correlation assumption may generally tend to over-estimate the amount of risk capital. This research also studies Copulas that can be used to model advanced dependence structure of operational risks beyond linear. The result shows that a copula can capture the nature of dependence that support the idea diversification benefit and would result in a significant reduction in operational risk capital.